The Influence of the Independent Curriculum on the Diverse Character of Junior High School Students 23 Pekanbaru - Rifandi, Aditya; Lubis, Aisyah; Nur, Apriza; Agustino, Dino; Istigfaroh, Halila; Rahmatullaila, Fitri; Hambali, Hambali (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the implementation of the Independent Curriculum on the development of diverse character among students at SMP Negeri 23 Pekanbaru. The Independent Curriculum emphasizes project-based learning that focuses on strengthening the Pancasila Student Profile, one of which is the value of global diversity. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and distribution of questionnaires to teachers and students. This research was conducted from September, October, and November. The results show that the implementation of the Independent Curriculum has a positive impact on attitudes of tolerance, cooperation, and respect for differences among students. Through project activities and collaboration, students become more open to cultural diversity and opinions. In conclusion, the Independent Curriculum plays an important role in developing students' diverse character, so it needs to be continuously developed in the school environment.